Ушебтi Панефернефера з колекцiї Полтавського краєзнавчого музею - Тарасенко, М.О. (Археологія, 2020)
Публікується давньоєгипетська заупокійна статуеткаушебті із полтавської музейної колекції. Це ушебті датується XXI династією і належало чоловіку на ім’я Панефернефер (старе читання Панеферхер). Він мав доволі
рідкісний титул «головний хранитель документів казначейства (Дома) Амона», який вказує на належність цієї
особи до кліру фіванського жрецтва. Статуетка була
придбана в 1894 р. П. П. Бобровським у Залі продажів
Каїрського Музею старожитностей. Публикуется древнеегипетская заупокойная статуэтка-ушебти из собрания Полтавского краеведческого музея
имени Василия Кричевского, инв. № А.149/1. Данное ушебти датируется XXI династией. Статуэтка была приобретена в 1894 г. П. П. Бобровским в Зале продаж Каирского Музея древностей для собрания Естественнонаучного музея Полтавского земства.
На лицевой стороне ушебти сохранилась иероглифическая надпись: «Просветленный, Осирис, главный
хранитель документов казны [храма] Амона Панефернефер, правогласный». О. Д. Берлев некорректно прочитал имя владельца ушебти А.149/1 как «Панеферхер», но правильным будет чтение Панефернефер (PA-nfr-nfr).
Владелец ушебти имеет редкий титул «главный хранитель документов сокровищницы храма Амона». Кроме
Панефернефера, известно еще пять жрецов, носивших этот титул. Все они жили в период XX и XXI династий,
что указывает на функционирование данного архива именно во времена этих двух династий. Данных о генеалогии Панефернефера нет.
К ушебти ПКМВК № А.149/1 имеется ряд аналогий: Copenhagen A.A.b.98 , A.A. 11 (?), Florence 6594—6596,
Ipswich R.1932—26.20; London BM EA 8906, EA 22790, Birmingham inv. no. ECM 376, Amasis Collection, inv. no.
S—2058. Помимо ушебти, сохранились и другие предметы погребального инвентаря Панефернефера: свиток
Книги мертвых (Vienna ÄS 3860), ящик для ушебти (Avignon A.82), модель саркофага (Berlin ÄM 6747) и две планки от ящика (Berlin ÄM 777 и 779). Кроме того, имя Панефернефера встречается на источниках, не имеющих
отношения к его погребальному инвентарю. Это письмо самого Панефернефера писцу Чари (pTurin 1979) и два
упоминания на саркофагах царей Аменхотепа I и Тутмоса II из тайника мумий в Дейр эль-Бахри (ТТ 320), которые
подтверждают, что Панефернефер принимал участие в мисси перезахоронения царских останков.
Памятники Панефернефера сохранили ряд титулов, дающих дополнительные просопографические данные,
в том числе и относительно его профессиональных обязанностей: «божий отец Амона», «писец двойной казны
храма Амона-Ра», «царя богов начальник ювелирных мастерских Амона», «начальник [///] Амона в Ипет-сут»,
«писец ювелирных мастерских Амона», «начальник работ».
Большинство предметов Панефернефера были приобретены европейскими коллекционерами в XIX в. Часть
из них попала в музейные собрания Великобритании, Германии, Дании и Украины, а часть находится в частных
коллекциях. Полтавское ушебти ПКМВК № А.149/1 является единственным памятником Панефернефера в Восточной Европе. The author publishes an ancient Egyptian funeral shabti-statuette from the collection of the Vasyl Krychevskyi Poltava
Local History Museum with inv. no. A.149/1 (blue faience, 9 × 3 × 2 cm). The shabti can be dated by the 21st Dynasty. The
figurine was purchased in 1894 by P. Bobrovskyi in the Sales Hall of the Cairo Museum of Antiquities for the collection of
the Natural Science Museum of the Poltava Regional Community.
The hieroglyphic inscription is preserved on the front side of the shabti: «Enlightened, Osiris, the Chief of the archivists
of the Treasury of the Temple of the Amun, Panefernefer, true-voiced». O. Berlev incorrectly read the name of the shabti
owner no. A.149/1 as «Paneferher», but the reading as Panefernefer (PA-nfr-nfr) is correct. The owner of the shabti has a rare
title «the Chief of the archivists of the Treasury of the Temple of the Amun». Besides Panefernefer, five more priests who
wore this title are known. All of them lived during the 20th and 21st Dynasties and that fact indicates the functioning of this
archive precisely at the time of these two dynasties. There is no data on the genealogy of Panefernefer.
There is a number of analogies to the shabti no. A.149/1: Copenhagen A.A.b.98, A.A.11 (?), Florence 6594—6596,
Ipswich R. 1932—26.20; London BM EA 8906, EA 22790, Birmingham inv. no. ECM 376, Amasis Collection, inv.
no. S—2058. In addition to shabtis, other objects of Panefernefer funeral assemblage are also preserved: a roll of the Book
of the Dead (Vienna ÄS 3860), a shabti-box (Avignon A.82), a sarcophagus model (Berlin ÄM 6747), and two planks of the
box (Berlin ÄM 777 and 779). Moreover, the name Paneferenfer is found on sources not related to his funeral inventory.
This is the letter of Panefernefer to the scribe Chari (pTurin 1979) and two references on the coffins of kings Amenhotep I
and Thutmose II from the mummy cache at Deir el-Bahri (TT 320), which confirm that Panefernefer took part in the
mission of reburying the royal remains.
Monuments of Panefernefer kept a number of titles that provide additional prosopographic information, including his
professional duties: «the divine father of the Amun», «the scribe of the double treasury of the temple of the Amun-Re, the king of the gods», «the head of the jewelry workshops of the temple of the Amun», «the head [///] Amun in Ipet-sut (Karnak
temple)», «the scribe of the jewelry workshops of the temple of the Amun», «head of the works».
Most of the artifacts of Panefernefer were acquired by European collectors in the 19th century. Some of them went
to museum collections in the UK, Germany, Denmark and Ukraine, and some are in private collections. Poltava shabti
no. A.149/1 is the only Panofernefer’s object in Eastern Europe.